2012
DOI: 10.1016/j.celrep.2012.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of 6,300 Genomic Fragments for cis-Regulatory Activity in the Imaginal Discs of Drosophila melanogaster

Abstract: 6,334 fragments from the genome of Drosophila melanogaster were analyzed for their ability to drive expression of GAL4 reporter genes in the 3rd instar larval imaginal discs. 1,194 reporter genes drove expression in the eye, antenna, leg, wing, haltere, or genital imaginal discs. The patterns ranged from large regions to individual cells. About 75% of the active fragments drove expression in multiple discs; 20% were expressed in ventral, but not dorsal, discs (legs, genital, and antenna), while ~23% were expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 36 publications
3
101
0
Order By: Relevance
“…2 D and G). These results are consistent with a recent survey describing a large collection of imaginal disc enhancers of D. melanogaster (Flylight) (26). Because the Wnt6 expression pattern is mostly similar to that of wg (27), and the clustering of four Wnt genes is conserved in the Drosophila genus, the loci have been inferred to share regulatory elements (28).…”
Section: Resultssupporting
confidence: 79%
“…2 D and G). These results are consistent with a recent survey describing a large collection of imaginal disc enhancers of D. melanogaster (Flylight) (26). Because the Wnt6 expression pattern is mostly similar to that of wg (27), and the clustering of four Wnt genes is conserved in the Drosophila genus, the loci have been inferred to share regulatory elements (28).…”
Section: Resultssupporting
confidence: 79%
“…However, we have not been able to detect Optix expression in the embryonic primordium of the eyeantennal disc, marked with the disc primordium marker ey-Z and using either an anti-Optix antiserum or the OptixNP2631-GAL4 line (not shown). We have also analyzed the expression of all available regulatory constructs associated with the Optix locus generated by the Janelia Project (Jory et al, 2012). Neither of the lines expressed in the eye disc showed overlapping expression with the embryonic eye primordium (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The UAS/GAL4 system (Brand and Perrimon, 1993) was used for most gain-and loss-of-function assays. We used oc2-GAL4 (Blanco et al, 2009), 86C11-GAL4 (Jory et al, 2012), hh-GAL4 (Tanimoto et al, 2000) and OptixNP2631-GAL4 (Hayashi et al, 2002) lines, all of which showed expression in different domains of the dorsal head during larval development. UAS lines used were: UAS-Arm S10 (UAS-Arm*) (Pai et al, 1997), UAS-Hh 6.1 , UAS-Optix S1 (26806, Bloomington Stock Center) and UAS-en (Guillen et al, 1995) for the ectopic expression experiments; and UAS-enRNAi and UAS-OptixRNAi (35697 and 31910, Bloomington Stock Center) for the knockdown inductions.…”
Section: Xho25mentioning
confidence: 99%
“…iCasper can also be used to examine spatiotemporal dynamics of apoptosis in a number of diseases including cancer. Moreover, iCasper may be used to study apoptosis in cell-typespecific lineage tracing during normal and disease development when combined with the large number of recently developed GAL4 lines (30)(31)(32). iCasper will also be useful to dissect signaling networks that lead to apoptosis by high-throughput screening using cultured cells or small animals.…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%
“…iCasper represents a useful tool for future studies examining molecular mechanisms of cancer, as well as lineage tracing of specific types of cells during normal and tumor development when combined with the large number of recently developed GAL4 lines (30)(31)(32).…”
Section: Infrared Fluorescent Executioner-caspase Reporter Visualizesmentioning
confidence: 99%